Surface profile study in construction area and existing building - Zahari N.M.; Razali S.S.M.; Nurhikmah F.; Aziz N.A.; Zawawi M.H.; Isa M.R.; Syamsir A. (American Institute of Physics Inc., 2024)
During the pre-building preparation for any construction site, topography and technical features of a location will be addressed. Nevertheless, most of those technologies that used produce digital topography models rely heavily on project site surveys. Digital Elevation Model (DEM) is a unique set of data that imitates a base elevation among established topographic points. DEM portrays a topographical base quantitative matrix in an electronic format. This study using a College of Engineering construction site in Universiti Tenaga Nasional (UNITEN) as an existing building for the field study. This study is carried out to measure a surface profile from Digital Elevation Model. The data obtained was converted to aerial mapping using Unmanned Aerial Vehicle (UAV) before process into Digital Elevation Model (DEM). The images was rendered using Agisoft Metashape software. After all photo from mutirotor drone was aligned, Digital Elevation Model (DEM) can be generated from the software. The measurements that were done are such as point coordinates, distances and profiles. 2023 Author(s).